Willingness to Pay for Environmental Quality: The Effects of Pro-Environmental Behavior, Perceived Behavior Control, Environmental Activism, and Educational Level. (November 2021) - Vicente, Paula; Marques, Catarina; Reis, Elizabeth
Environmental quality is one of the major concerns in contemporary societies. The main goal of this research is to investigate citizens' willingness to pay for environmental quality and whether this propensity differs in line with education level. Structural equation modeling is used to explore the associations between several constructs; specifically, a multigroup analysis is conducted to assess the invariance of two educational level segments. Results suggest that willingness to pay more for environmental quality is positively associated with perceived behavior control and environmental activism. Pro-environmental behavior does not impact willingness to pay for environmental quality but is positively related to perceived behavior control and environmental activism. The relationships between constructs hold true for both groups of education. Implications for public policy and marketing actions are addressed.